Decreased Plasma Nesfatin-1 Level Is Related to the Thyroid Dysfunction in Patients with Type 2 Diabetes Mellitus - Fupeng Liu; Qing Yang; Ning Gao; Fangfang Liu; Shaohua Chen (Journal of Diabetes Research)
Aims. Thyroid dysfunction is frequently observed in patients with type 2 diabetes mellitus (T2DM), but the underlying mechanism is still poorly understood. The present study aimed to investigate whether nesfatin-1 played a role in the thyroid dysfunction in patients with T2DM. Methods. 55 euthyroid patients were enrolled in this study including 30 patients with T2DM and 25 patients with impaired glucose regulation (IGR). 30 age-matched healthy people were also included as the control. The plasma levels of nesfatin-1, thyrotropin (TSH), and glycosylated hemoglobin (HbA1c) as well as the body mass index (BMI) were comparatively analyzed among the three groups. Results. The nesfatin-1 was significantly lower in patients with T2DM than in patients with IGR and in the control. On the contrary, the TSH level was significantly higher in patients with T2DM than in patients with IGR and in the control. Simple regression analysis showed that the plasma nesfatin-1 was negatively correlated with the TSH and HbA1c levels and positively correlated with the BMI. With multiple stepwise regression analysis, the nesfatin-1 remained to be independently correlated with the TSH, BMI, and HbA1c. Conclusions. The study was suggesting a role of nesfatin-1 in thyroid dysfunction in patients with T2DM.